The Fowl twins get what they deserve - Colfer, Eoin (Colfer, Eoin. Fowl twins (Series), 2021)
"Twins Myles and Beckett face off against Lord Teddy Bleedham-Drye, the Duke of Scilly, who has been plotting revenge against them since they humiliated him"--